Improved Analgesic and Anti-Inflammatory Effect of Diclofenac Sodium by Topical Nanoemulgel: Formulation Development—In Vitro and In Vivo Studies. (21st April 2020) - Md, Shadab; Alhakamy, Nabil A.; Aldawsari, Hibah M.; Kotta, Sabna; Ahmad, Javed; Akhter, Sohail; Shoaib Alam, Md; Khan, Mohammad A.; Awan, Zuhier; Sivakumar, Ponnurengam Malliappan
Abstract : The present study aimed to develop diclofenac sodium nanoemulgel for managing pain and inflammation using the low-energy emulsification technique. Nanoemulsion of diclofenac was formulated using clove oil with adequate amount of surfactants and cosurfactants, and it was converted to hydrogel form using Carbopol 980 as the gelling agent. The droplet size of the oil globules in the nanoemulsion was found to be 64.07 ± 2.65 nm with a low polydispersity index (0.238 ± 0.02) along with high negative zeta potential (−39.06 mV). The developed nanoemulgel exhibited non-Newtonian and pseudoplastic behavior. The in vitro release profile of the developed nanoemulgel was higher as compared to marketed and conventional gel. The carrageenan-induced paw edema test was performed in rats to evaluate the anti-inflammatory activity of developed nanoemulgel. The developed nanoemulgel showed significantly higher (p < 0.01 ) effect in reducing pain and inflammation symptoms as compared to marketed as well as conventional gel of diclofenac. The overall findings of the study suggest that the developed nanoemulgel formulation of diclofenac can be used as a potential approach for the management of pain and inflammation.